Assessment of Clarias batrachus as a source of acetylcholinesterase (AChE) for the detection of insecticides - Tham, Lik Gin; Perumal, Natarajan; Syed, Mohd Arif; Shamaan, Nor Aripin; Abd. Shukor, Mohd. Yunus (Triveni Enterprises, 2009)
An inhibitive assay of insecticides using Acetylcholinesterase (AChE) from the local fish Clarias batrachus is reported. AChE was assayed according to the modified method of Ellman. Screening of insecticide and heavy metals showed that carbofuran and carbaryl strongly inhibited C. batrachus AChE. The inhibition concentration (IC) IC50 values (and the 95% confidence interval) for both carbofuran and carbaryl inhibition on C. batrachus AChE at 6.66 (5.97-7.52) and 130.00 (119.3-142.5) mg l-1, respectively, was within the IC50 range of Electrophorus electricus at 6.20 (6.03-6.39) and 133.01 (122.40-145.50) mg l-1, respectively, and were much lower than bovine AChE at 20.94 (19.53-22.58) and 418.80 (390.60-451.60) mg l-1, respectively. The results showed that C. batrachus have the potential to be used as a cheaper and more readily available source of AChE than other more commercially available sources.